Hantavirus Pulmonary Syndrome: Report of the First Canadian Paediatric Case. (1998) - Lee, Bonita E; Joffe, Ari R; Vaudry, Wendy
Abstract : Hantavirus pulmonary syndrome (HPS) was first recognized as a severe respiratory illness transmitted through rodent excreta in the southwestern United States in 1993. As of November 1997, 175 cases have been reported in the United States. The mortality rate of this disease has been reported to be as high as 52% in the United States, and the majority of the cases (94%) involved adults. Twenty-one cases have been recognized in Canada. This paper describes the first Canadian paediatric case and discusses some of the clinical features of this disease.